Models of University Interaction with the Economy and Social Sphere of the Region - E. Ya. Kogan; N. Yu. Postalyuk; T. G. Kuteinitsyna (Высшее образование в России)
The purpose of this work is to summarize and typologize ways and forms of organizing the interaction between the domestic system of higher education and regional markets. The authors focus on the forms of interaction organization between higher education institutions and labor market at the regional level associated with their regional specifics. The basic principles of interaction between regional systems of higher education and business community (focus on meeting the needs of the economy, collegial, open and mutually beneficial nature of cooperation) and the existing experience of various subjects of the Russian Federation are discussed, taking into account the specifics of their own regional situation. The article dwells on the characteristics of the current level of innovation and entrepreneurial activity of Russian universities, systematizes the practices coordinating the needs of the economy and the organization of higher education in the field of personnel and technological support of the regional economy. The authors discuss the models of joint activities of universities, business communities and regional authorities institutionalization in the interests of socio-economic development of the subject of the Russian Federation, as well as two major components of the impact of higher education on the economy and social sphere of the region, namely the adequate staffing for the development of the region and the commercialization of R & D / R & D products of universities in the innovation sphere of the regions. It is shown that the level of regional involvement of universities in the development of the business environment, projects and programs that operate in the interests of local communities is different, and its institutionalization is diversified. In this connection, it is proposed to harmonize the needs of the economy and the activities of universities in the field of meeting personnel demands and developing new production technologies, combining the efforts of the executive authorities and specialized intermediary structures. The article argues the necessity of the formation of a specialized interface in the structure of a higher education institution that ensures the orientation of scientific and educational activities of higher education institutions towards the prospective demands of the regional economy.